The IS2 Element Improves Transcription Efficiency of Integration-Deficient Lentiviral Vector Episomes - Sabina Sánchez-Hernández; Alejandra Gutierrez-Guerrero; Rocío Martín-Guerra; Marina Cortijo-Gutierrez; María Tristán-Manzano; Sandra Rodriguez-Perales; Laura Sanchez; Jose Luis Garcia-Perez; Jesus Chato-Astrain; Ricardo Fernandez-Valades; Ana Belén Carrillo-Galvez; Per Anderson; et al. (Elsevier, 2018)
Integration-defective lentiviral vectors (IDLVs) have become an important alternative tool for gene therapy applications and basic research. Unfortunately, IDLVs show lower transgene expression as compared to their integrating counterparts. In this study, we aimed to improve the expression levels of IDLVs by inserting the IS2 element, which harbors SARs and HS4 sequences, into their LTRs (SE-IS2-IDLVs). Contrary to our expectations, the presence of the IS2 element did not abrogate epigenetic silencing by histone deacetylases. In addition, the IS2 element reduced episome levels in IDLV-transduced cells. Interestingly, despite these negative effects, SE-IS2-IDLVs outperformed SE-IDLVs in terms of percentage and expression levels of the transgene in several cell lines, including neurons, neuronal progenitor cells, and induced pluripotent stem cells. We estimated that the IS2 element enhances the transcriptional activity of IDLV LTR circles 6- to 7-fold. The final effect the IS2 element in IDLVs will greatly depend on the target cell and the balance between the negative versus the positive effects of the IS2 element in each cell type. The better performance of SE-IS2-IDLVs was not due to improved stability or differences in the proportions of 1-LTR versus 2-LTR circles but probably to a re-positioning of IS2-episomes into transcriptionally active regions. Keywords: IDLV, HS4 insulator, gene therapy, scaffold or matrix attachment regions, lentiviral vector